2021
DOI: 10.3126/ajms.v12i4.33343
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis, An inflammatory condition associated with oxidative stress

Abstract: Background: Psoriasis is a chronic inflammatory skin disease characterized by pathological skin lesions due to various exogenous and endogenous factors. Oxidative stress can be one of the causes for the occurrence of psoriasis as well as significant contributor to its progression. Skin exposure to a number of irritants or proinflammatory agents including UVA and UVB generates ROS through the oxidative burst in infiltrating leukocytes at the site of inflammation which damages the skin cells. Measurement of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Firstly, the cellular safety of all TEs used was known from the MTT results. Oxidative stress may be one of the reasons for the development of psoriasis [ 39 ]. ROS have been reported to damage cellular components and its increased production has been linked to the pathogenesis of psoriasis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the cellular safety of all TEs used was known from the MTT results. Oxidative stress may be one of the reasons for the development of psoriasis [ 39 ]. ROS have been reported to damage cellular components and its increased production has been linked to the pathogenesis of psoriasis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also suggested that the onset and perpetuation of psoriatic inflammation may be associated with oxidative stress [ 57 , 58 ]. Therefore, it seems reasonable to take into account a balanced diet rich in antioxidants as an important tool in psoriasis management [ 59 ].…”
Section: Genistein As a Biologically Active Plant Compoundmentioning
confidence: 99%
“…Çalışmada psöriyazis patogenezinde oksidatif stresin önemli rol oynadığı ve hastalıktaki inflamatuar sürecin bir göstergesi olabileceği ifade edilmiştir. 26 Çalışmamızda, ortalama NO 2 ve NO 3 düzeyleri, hasta grubunda kontrol grubuna oranla yüksek bulunmuş, ancak bu yükseklik istatistiksel olarak anlamlı bulunmamıştır. Ortalama NO 2 ve NO 3 değerleri şiddetli hastalık grubunda kontrol ve hafif gruba oranla istatistiksel olarak anlamlı derecede yüksek bulundu.…”
Section: Bulgularunclassified